The use of gamma and weibull distributions in modeling rainfall data in Nigeria (a comparative analysis) (2010)
The distribution of rainfall in Nigeria is not uniform due to the slight differences in the climatic conditions from one geographical region to the other. The climatic conditions ranges from the ‘very wet’ mangrove forest zone of the coastal areas, especially the South-South, to the semi arid regions of the North- West and North-East that share boundaries with the ‘very hot’ desert zone of the North Africa subcontinent. Rainfall data are examples of environmental data, which generally can be modeled by the family of exponential distributions. The Weibull probability function is the most widely used in fitting the distribution of rainfall. This study compares the results obtained by this function with another distribution proposed to the African scientists, that is, the gamma probability function by employing the Kolmogorov- Smimov (K-S) one sample test in testing the goodness- of-fit of these distributions. The results provided are useful tools for decision makers in hydrological and related establishments.